Factors Associated with Physical Activity among Study Participants at Buho-Buho Primary Health Center, Pulau Morotai Regency - Abas, Fahrudin M; Nurmayunita, Heny; Asri, Yuni (Jurnal Kesehatan, 2026)
Introduction: Physical activity plays an important role in maintaining health and preventing non-communicable diseases. However, levels of physical activity are influenced by various demographic and lifestyle factors, particularly in primary healthcare settings. Objective: This study aimed to analyze factors associated with physical activity among study participants at Buho-Buho Primary Health Center, Pulau Morotai Regency Method: This study employed an analytical observational design with a cross-sectional approach. A total of 69 participants were included using a total sampling technique. Physical activity was categorized as active and physically inactive. Independent variables included demographic characteristics (gender, age group, marital status, educational level, and employment status) and lifestyle factors (smoking habits). Data were analyzed using SPSS version 26. Descriptive analysis was presented as frequencies and percentages, while bivariate analysis was conducted using the Chi-square test or Fisher’s exact test, with a significance level of p < 0.05. Results: The results showed that gender (p = 0.013), age group (p < 0.001), employment status (p = 0.020), and smoking habits (p = 0.006) were significantly associated with physical activity. Marital status and educational level were not significantly associated with physical activity. Conclusion: Physical activity was significantly associated with gender, age group, employment status, and smoking habits among study participants. These findings highlight the importance of considering demographic and lifestyle factors in promoting physical activity at the primary healthcare level.